Ferric ion substitution renders cadmium metal–organic framework derivatives for modulated Li storage based on local oxidation active centers. Issue 3 (23rd December 2022) - Jiang, Wei; Gao, Baihui; Yan, Guosong; Xu, Shichong; Chu, Xianyu; Che, Guangbo; Liu, Bo; Lu, Ming; Liu, Chunbo
Abstract : Fe 3+ substituted Cd-based metal–organic framework deriving carbon-coated Fe3 O4 /Fe hybrid renders ion precise modulation to build local redox centers, exhibiting high Li + storage performance. Abstract : In this work, a novel anionic Cd-MOF ([(CH3 )2 NH2 ] n [Cd(HL)DMF] n ·2 n H2 O·nDMF, H4 L = 1, 2, 4, 5-tetrakis[(4-carboxy)phenoxymethyl]benzene) was synthesized for the first time. As a precursor, it was utilized to obtain Fe@Cd-MOF crystals via the substitution of Fe 3+ ions due to a negatively charged framework and free-coordinated carboxyl group. Fe3 O4 /Fe-embedded carbon-based materials (Fe@Cd-MOFD ) were further constructed by deriving Fe@Cd-MOF at high temperatures. The derived Fe@Cd-MOFD showed a structure resembling a central city with metal redox centers embedded into a carbon matrix. The introduced Fe 3+ ions formed a local nano-sized metal oxide upon annealing, and these derived carbon materials offered high electronic conductivity. These pushed Fe@Cd-MOFD to remarkable electrochemical performance with an initial discharge capacity of 1703.8 mA h g −1 . This work offers new insights into the fabrication of novel MOF-derived iron oxide hybrids for lithium storage.